Exchange market pressure : empirical investigation on East Asian nation - Yong, Jenny Lijoo (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study seeks to examine three issues of external debt, specifically (1) external debt determination; (2) external debt and economic growth nexus; and (3) external debt sustainability in three ASEAN countries, namely Malaysia, the Philippines and Thailand. Due to certain data availability, the time frames for all the countries are different for each issue. Malaysia, Thailand and the Philippines utilize times series data spanning from 1970-2012, 1977-2012 and 1976-2012, respectively for issue one. As for second and third issues, the time frames are 1970-2012 for Malaysia; 1980- 2012 for Thailand and 1985-2012 for the Philippines. In this study, several statistical tests are employed. Firstly, Augmented Dickey-Fuller (ADF) and Kwiatkowski, Phillips, Schmidt and Shin (KPSS) unit root tests are implemented to test the stationarity of the variables. Secondly, Johansen and Juselius (1990) multivariate cointegration analysis is adopted to examine the long run cointegration relationship among the variables. Next, Granger causality in vector error correction model (VECM) is conducted to examine the causality relationship among the variables. Lastly, the dynamic analysis including variance decompositions (VDCs) and impulse response functions (IRFs) are utilized to gauge the relative strength of the variables. The empirical results obtained indicate an existence of unidirectional causation from inflation rate to external debt for both Malaysia and the Philippines. Apart from that, the results of dynamic analysis show that inflation rate is the most endogenous variables for all the countries, while real interest rate, nominal GDP and external debt are the most exogenous variable for Malaysia, Thailand and the Philippines respectively. The second aim is to examine the relationship between external debt and economic growth. The empirical results show that the speed of short run adjustment appears to have fallen mostly on economic growth, where economic growth is the cause for external debt, exports and budget balances for the three ASEAN countries. In order to test the fiscal reaction function, methodology developed by Bohn (1998) is adopted. This leads to a finding that Thailand has persistent positive fiscal reaction coefficient while Malaysia and the Philippines have negative fiscal reaction coefficient which indicate that the external debt was unsustainable during the sample period in this study.